2016
DOI: 10.1111/nous.12151
|View full text |Cite
|
Sign up to set email alerts
|

Moral Disagreement and Moral Semantics

Abstract: When speakers utter conflicting moral sentences (“X is wrong”/“X is not wrong”), it seems clear that they disagree. It has often been suggested that the fact that the speakers disagree gives us evidence for a claim about the semantics of the sentences they are uttering. Specifically, it has been suggested that the existence of the disagreement gives us reason to infer that there must be an incompatibility between the contents of these sentences (i.e., that it has to be the case that at least one of them is inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
74
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(81 citation statements)
references
References 78 publications
(94 reference statements)
3
74
0
Order By: Relevance
“…Recall the experimental findings of a statistically significant resistance in ordinary subjects toward the use of markers like 'incorrect', 'wrong', and 'false' in the context of (clearly and explicitly) fundamental disagreements (Sarkissian et al 2011, Khoo & Knobe 2016. Such a reticence fits well with the QED account of these disagreement, given the observed datum that mere conflicts in attitudes (as in exchange (2)) do not in general license such use.…”
Section: The Case Against Mldmentioning
confidence: 52%
See 2 more Smart Citations
“…Recall the experimental findings of a statistically significant resistance in ordinary subjects toward the use of markers like 'incorrect', 'wrong', and 'false' in the context of (clearly and explicitly) fundamental disagreements (Sarkissian et al 2011, Khoo & Knobe 2016. Such a reticence fits well with the QED account of these disagreement, given the observed datum that mere conflicts in attitudes (as in exchange (2)) do not in general license such use.…”
Section: The Case Against Mldmentioning
confidence: 52%
“…So it is suggested that it is actually the absolutist, not the relativist, who has some explaining to do. As Khoo and Knobe (2016) put it, "not only is it not problematic for a theory if it fails to predict exclusionary content in all cases of moral disagreement, but it is problematic for a theory if it does predict exclusionary content in all cases of moral disagreement." 5 I know this claim will raise some eyebrows, 6 so while it isn't my purpose in this paper to argue for the strategy, I'll quickly list some of the kinds of evidence I have in mind:…”
Section: Content-relativists Have Typically Responded To the Problem mentioning
confidence: 99%
See 1 more Smart Citation
“…Other authors have developed Discursive Disagreement in a contextualist framework. For example, some have proposed that Ava and Bert are involved in a metalinguistic dispute about how to set the value of a conversational standard of taste parameter (Plunkett and Sundell ; Barker ; for similar ideas, see DeRose ; Khoo ; Khoo and Knobe ; Silk ). Thus in uttering (3a), Ava proposes to set the standard of taste parameter in such a way that the escargot falls under the extension of tasty .…”
Section: Subjective Disagreement As Discursive Disagreementmentioning
confidence: 99%
“…And so, some may suggest, we should recast the Discursive Account as a dispositional theory, e.g. : Discursive Account of Speechless Disagreement (Dispositional) Two parties have a speechless disagreement over some subjective matter M iff they are disposed to have a discursive disagreement over M . (See Khoo and Knobe , fn. 21 for a suggestion along these lines.)…”
mentioning
confidence: 99%